Atitudes parentais sobre o papel do convívio com animais no desenvolvimento sociocognitivo de crianças - Chiari, Ana Paula dos Santos (Universidade Federal de São Carlos, 2024)
There is substantial evidence of the positive effects of living with siblings, peers, and friends on sociocognitive development; however, the number of studies investigating the effects of living with animals is still limited. The present study aimed to contribute in this direction by exploring parental attitudes on the role of living with pets in their children's development. A questionnaire was sent (via Google Forms) to 30 fathers and/or mothers of children aged 2 to 5 10 years who currently live or have lived with animals at home. The questionnaire included questions related to how parents perceive their children's relationships with family, friends, and animals, as well as the possible beneficial effects and/or disadvantages of living with animals at home. The vast majority of parents (90%) did not report any disadvantages of living with pets. On the contrary, they indicated several advantages, such as learning, companionship, play, and the development of sociocognitive and social skills. Furthermore, when asked if they believed that living with animals influenced how their children interacted with others, most parents (73.3%) said yes. A thematic analysis of responses to open-ended questions revealed the following observed benefits: improvements in health, learning and development, friendships, improved behavior, and reduction of fear responses. Overall, results suggest a very positive perspective from parents regarding the role of living with pets in their children's development. We hope that this data may contribute to the development of intervention programs and/or public policies aimed at promoting development in early and late childhood by means of this rich relationship between children and animals.
Parental attitudes on the role of living with pets on children's sociocognitive development
Keywords: Atitudes parentais; Desenvolvimento sociocognitivo; Animais; Parental attitudes; Sociocognitive development; Animals; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::DESENVOLVIMENTO SOCIAL E DA PERSONALIDADE